Analysis of Expression and Its Clinical Significance of the Secreted Phosphoprotein 1 in Lung Adenocarcinoma - Guo, Zixin; Huang, Jingyu; Wang, Yujin; Liu, Xiao-Ping; Li, Wei; Yao, Jie; Li, Sheng; Hu, Weidong (Frontiers in Genetics, 2020)
Objective: To explore the expression of secreted phosphoprotein 1 (SPP1) in lung adenocarcinoma (LUAD), and evaluate its relationship with clinicopathological characteristics and prognosis of LUAD, and analyze the advantages of SPP1 as a potential prognostic marker in LUAD. Methods: The expression of SPP1 in normal lung tissue and LUAD was analyzed from the CCLE, GEO and HPA databases. GSE68465 was used to explore the relationship between the SPP1 expression and clinicopathological characteristics and the prognosis of LUAD patients. The relationship between SPP1 and immune infiltration in LUAD was analyzed by TIMER database. Gene enrichment analysis was performed in GSEA. TCGA-LUAD data was used to verify the results. Results: In the cell line level, non-small cell lung cancer ranked the ninth among cancer cell lines based on SPP1 expression. In the mRNA level and protein level, SPP1 expression was higher in LUAD tissues than that in normal control. And SPP1 expression was related to gender, N stage, histologic grade and progression or relapse. In males, SPP1 expression were higher compared to females. And the higher the N stage, the higher the SPP1 expression level. As LUAD progresses or relapses, SPP1 expression could increase. In the pathological grade, the SPP1 expression was higher in LUAD samples with moderately differentiated. In addition, the overall 5-year survival rates of the SPP1 high and low expression groups were 50.574% and 59.181% (P=0.008, HR=0.7057, 95% CI:0.5467~0.9109), indicating that SPP1 had an impact on overall survival for LUAD patients. The relationship between SPP1 expression and CD4+T cell, macrophage, neutrophil, dendritic cell infiltration was weak in LUAD. SPP1 could be considered as an independent prognostic marker in LUAD (P=0.003, HR=1.150; 95%CI=1.048~1.261) by multivariate Cox regression analysis. The results of GSEA indicated that samples with high SPP1 expression were enriched in protein secretion, mTORC1 signaling, angiogenesis, and glycolysis pathway. The analysis results obtained by TCGA-LUAD data were basically consistent with the results obtained by GSE68465. Conclusions: SPP1 can not only affect the occurrence and development of LUAD, but also may be an independent prognostic marker of LUAD. SPP1 is expected to be a new target of molecular targeted therapy.